Changes in numbers and distribution of wintering waterbirds at the south coast of Scania, Sweden, during 55 winters, 1964–2018 - Nilsson, Leif (Ornis Svecica, 2020)
The south coast of Scania, southernmost Sweden, has long been an important wintering and staging area for waterbirds. A large part of the coast was surveyed annually as a part of the international midwinter counts for 55 years (1964–2018). The total number of wintering waterbirds showed an increasing trend but there was much variation between years. Common Goldeneye Bucephala clangula, followed by Mallard Anas platyrhynchos, Tufted Duck Aythya fuligula and—during the early years—Long-tailed Duck Clangula hyemalis, dominated the community. Great Cormorant Phalacrocorax carbo, Mallard, Common Goldeneye and Eurasian Coot Fulica atra increased in numbers, reflecting the national and international trends related to milder winters and a northward shift of the winter distribution. Eurasian Wigeon Mareca penelope and Great Crested Grebe Podiceps cristatus established wintering traditions in the area during the study period. Tufted Duck and Common Merganser Mergus merganser decreased locally due to a northward shift of the wintering distribution northwards within the country. The Long-tailed Duck was an important winter guest in the first years but was only seen in very small numbers in later years, reflecting the general and large-scale decrease of the Baltic wintering population.